Rheological Regimes in Agitated Granular Media under Shear - D'Angelo, Olfa; Sperl, Matthias; Kranz, W. Till (Physical Review Letters, 2025)
Agitated granular media have a rich rheology: they exhibit Newtonian behavior at low shear rate and density, develop a yield stress at high density, and cross over to Bagnoldian shear thickening when sheared rapidly - making it challenging to encompass them in one theoretical framework. We measure the rheology of air-fluidized glass particles, spanning 5 orders of magnitude in shear rate. By comparing fluidization-induced to Brownian agitation, we show that all rheological regimes can be delineated by two dimensionless numbers - the Péclet number, Pe, and the ratio of shear-to-fluidization power, Π - and propose a constitutive relation that captures all flow behaviors, qualitatively and quantitatively, in one unified framework.
CRIS-Team Scopus Importer:2025-04-18